2012
DOI: 10.1007/s00134-012-2676-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function in Ghanaian children with severe malaria

Abstract: Increased CI reflecting high output status is associated with low hemoglobin levels while metabolic acidosis is linked to parasite levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…The pathogenesis mechanisms of several diseases caused by protozoan and nematode parasites have shown to cause detrimental effect on cardiac and skeletal muscles (i.e., Chagas disease, toxoplasmosis, trichinosis, leishmaniosis, and malaria) [47]. Parasitic infestations by Trypanossoma cruzi , Toxoplasma gondii and Trichinella spiralis cause cardiomyopathy in the immunocompetent and immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis mechanisms of several diseases caused by protozoan and nematode parasites have shown to cause detrimental effect on cardiac and skeletal muscles (i.e., Chagas disease, toxoplasmosis, trichinosis, leishmaniosis, and malaria) [47]. Parasitic infestations by Trypanossoma cruzi , Toxoplasma gondii and Trichinella spiralis cause cardiomyopathy in the immunocompetent and immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…How these changes in the electrophysiology of the heart also influence cardiac function is difficult to say. While an impaired cardiac output in acidotic children could not be shown in the same study population [27] others indeed identified impaired cardiac function in relation to acidosis [27,28]. Children with hyperlactataemia and metabolic acidosis also showed increased HR.…”
Section: Discussionmentioning
confidence: 85%
“…The QT intervals were computed from the peak of the R to the peak of the T wave in a pseudo-ECG from Φ=a ∫(−∇V)(∇(1/x−x ′ ))dx (2) where Φ represents the unipolar potential recorded at an electrode 20 mm from the epi-cardial end of the strand, a is a scaling factor, and x − x′ is the distance from the electrode to any point in the tissue [11]. For both the adult and child models, the APD90s and QT intervals in ms were shorter in the malarial model than the normal, whereas the QTc was prolonged in the adult (from 257 to 310ms) and shortened in the child (from 274 to 172ms).…”
Section: Resultsmentioning
confidence: 99%
“…90% of these deaths are in were in sub-Saharan Africa, and 70% in children less than 5 years old. Cardiac function, in terms of rate, stroke volume, ejection fraction and haemodynamic indices is impaired in severe malaria [1][2][3], and some antimalarial agents (the quinolines) affect ventricular repolarization, observed as QT interval prolongation [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation